Differences in psychiatric symptoms among Asian patients with depression: a multi-country cross-sectional study - Sulaiman, A.H.; Bautista, D.; Liu, C.Y.; Udomratn, P.; Bae, J.N.; Fang, Y.; Chua, H.C.; Liu, S.I.; Geogre, T.; Chan, E.; Mei, S.T.; Hong, J.P.; et al. (2013)
Aim: The aim of this study was to compare the symptomatic and clinical features of depression among five groups of patients with major depressive disorder (MDD) living in China, Korea, Malaysia/Singapore,Taiwan, and Thailand. Methods: Consecutive consenting adults (aged 18– 65) who met DSM-IV criteria for non-psychotic MDD – based on the Mini International Neuropsychiatric Interview – and who were free of psychotropic medication were evaluated in a cross-sectional study.Depressive symptoms were evaluated using the 10-item Montgomery–Asberg Depression Rating Scale(MADRS) and the 13-item depression subscale of the Symptoms Checklist 90-Revised (SCL-90-R). In addition, the 10-item SCL-90-R Anxiety Subscale was completed.ANCOVA were conducted, adjusting for confounders: age, completion of secondary education,marital status, work status, religion, index episode duration, and depressive severity. For the magnitude of differences, a threshold of 0.10 was taken as the minimum effect size representing clinical significance, and an effect size of 0.25 was considered moderate. Results: Four MADRS symptoms differentiated these five groups, the most prominent being ‘lassitude’ and ‘inner tension’. Nine SCL-90-R depression items also differentiated the groups, as did eight SCL-90-R Anxiety Subscale items. The MADRS lassitude item had the largest effect size (0.131). The rest of those statistically significant differences did not exceed 0.10. Conclusion: MDD is more similar than different among outpatients in these diverse Asian countries. The between-country differences, while present and not due to chance, are small enough to enable the use of common clinician and self-report rating scales in studies involving Asians with MDD from various ethnic backgrounds.